From comparative literature to the study of mediators - Cedergren, Mickaëlle; Schwartz, Cecilia (Moderna Språk, 2016)
Introduction to this special issue of Moderna språk. This special issue of Moderna Språk contains articles on Swedish mediators who have introduced, translated and reviewed literary texts from the Romance languages. More specifically, the contributions are the outcome of the symposium ”Litteraturförmedlare i Sverige från 1945 till våra dagar” (’Literary mediators in Sweden from 1945 until today’) which took place at Stockholm University 11–12 June 2015.